Triple-helix knowledge-based Sino-Nordic Arctic relationships for trust and sustainable development - Bertelsen, Rasmus (Polar Research Institute of China - PRIC, 2016)
This paper goes beyond Sino-Nordic Arctic science diplomacy and looks at Sino-Nordic Arctic triple-helix knowledge based collaborations among academia, business, civil society (the inclusion of which moves beyond the original triple-helix concept), and government. In light of the potential of science diplomacy for building Sino-Arctic trust under systemic international conditions of power transition and globalization, this is the natural next step toward exploring triple-helix collaborations. Knowledge-based collaborations between academia, business, civil society, and government also open up avenues for innovation and entrepreneurship by both Arctic societies and Chinese society in attempts to address major challenges to sustainable development in these societies. This paper discusses possible triple-helix knowledge-based collaborations with China by each of the five Nordic countries, and highlights the innovation and entrepreneurial talents of summer school students at the University of International Relations in Beijing in developing projects as part of a course entitled “The Global Arctic”.